Residents’ Perceptions of Mountain Destinations - Silva, Carla (2015)
This chapter analyses residents’ perceptions of mountain destinations. The aim is to develop a scale for assessing residents’ mountain images. An extensive literature review and insights from an empirical study of 315 residents of the Serra da Estrela in Portugal, the Alps in France, Austria and Switzerland, and the Peaks of Europe in Spain show that mountain images held by local people refer to the dimensions: mystic/sacred, historic-cultural life; health and affective image. Results were obtained by both content analysis of open-ended questions and by a quantitative approach based on scale items identified as belonging to specific dimensions in the literature review, whose relevance was confirmed through a confirmatory factor analysis using LISREL. Discussion is focused on theoretical and practical implications of findings and limitations are also presented.